Predicting purchasing intention through a single stage siamese deep learning models - Takano, Kevin Kimiya (Universidade Federal do Amazonas, 2022)
Understanding consumer buying behavior in the context of e-commerce is a recent trend at large retail stores. It can be very attractive for retail companies to know which users will buy in their market and what products they will buy. Through the study of online user behavior, models can be created to improve marketing personalizing, and build digital products.